International Conference on Security and Privacy in Communication Networks. 10th International ICST Conference, SecureComm 2014, Beijing, China, September 24-26, 2014, revised selected papers /: 10th International ICST Conference, SecureComm 2014, Beijing, China, September 24-26, 2014, revised selected papers. Part II : (2015) - Unknown
No abstract available